Molecular Signatures of Neuroinflammation Induced by αSynuclein Aggregates in Microglial Cells - Sarkar, Souvarish; Dammer, Eric B.; Malovic, Emir; Olsen, Abby L.; Raza, Syed Ali; Gao, Tianwen; Xiao, Hailian; Oliver, Danielle L.; Duong, Duc; Joers, Valerie; Seyfried, Nicholas; Huang, Meixiang; et al. (Frontiers in Immunology, 2020)
Alpha-synuclein aggregates (α-synAgg) are pathological hallmarks of Parkinson's disease (PD) and other synucleinopathies that induce microglial activation and immune-mediated neurotoxicity, but the molecular mechanisms of α-synAgg-induced immune activation are poorly defined. We performed quantitative proteomics by mass spectrometry coupled with PCR, immunohistochemical and functional validations studies to define the molecular characteristics of alpha synuclein mediated microglial activation. In mouse microglia, α-synAgg induced robust pro-inflammatory activation (increased expression of 864 genes including Irg1, Ifit1 and Pyhin) and increased nuclear proteins involved in RNA synthesis, splicing and anti-viral defense mechanisms. Conversely, α-synAgg decreased expression several proteins (including Cdc123, Sod1 and Grn), which were predominantly cytosolic and involved in metabolic, proteosomal and lysosomal mechanisms. Pathway analyses and confirmatory in vitro studies suggested that α-synAgg partly mediates its effects via Stat3 activation. As predicted by our proteomic findings, we verified that α-synAgg induces mitochondrial dysfunction in microglia. 26 proteins differentially expressed by α-synAgg were also identified as PD risk genes in genome-wide association studies (upregulated: Brd2, Clk1, Siglec1; down-regulated: Memo1, Arhgap18, Fyn and Pgrn/Grn). We then validated progranulin (PGRN) as a lysosomal PD-associated protein that, relative to the vast upregulation of activated microglia, is decreased in nigral microglia in post-mortem PD brain compared to non-disease controls, congruent with our in vitro findings.Together, proteomics approach both reveals novel molecular insights into α-syn-mediated neuroinflammation in PD and other synucleinopathies.